Discharge planning improved quality of life on stroke patient: a review - Laila, Nida; Armiyati, Yunie; Soesanto, Edy (Riset Informasi Kesehatan, 2024)
Background: Discharge planning in stroke patients represents a novel evidence-based intervention strategy when implemented in a systematic and comprehensive manner. The integration of several evidence-based standards or elements has the potential to enhance the clinical outcomes of stroke patients. The objective of this study was to ascertain the evolution of research on discharge planning in stroke patients over the past five years (2019-2024). Method: This research employed a literature review design with a database article search method on EBSCO, ScienceDirect, and PubMed. Result: The majority of the subjects studied were patients with acute stroke disease, and the results of the study demonstrated effective outcomes for the variables under investigation. Conclusion: The literature that indicate the potential of interventions to improve clinical outcomes and quality of life in stroke patients